2014
DOI: 10.1039/c4ee02575j
|View full text |Cite
|
Sign up to set email alerts
|

A quinone-based oligomeric lithium salt for superior Li–organic batteries

Abstract: Organic electrode materials are promising alternatives to transition-metal based intercalation compounds for the next generation of high-performance and sustainable batteries. Herein, a novel quinone-based organic, lithium salt of poly(2,5-dihydroxy-p-benzoquinonyl sulfide) (Li 2 PDHBQS), was successfully synthesized through a simple one-step polycondensation reaction, and applied as a cathode for Li-organic batteries. As an oligomeric lithium salt with average polymerization degree of 7, Li 2 PDHBQS combines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
300
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(309 citation statements)
references
References 40 publications
(102 reference statements)
7
300
2
Order By: Relevance
“…According to molecular orbital theory, a lower lowest unoccupied molecular orbital (LUMO) energy means a larger electron affinity and higher reduction potential, while the LUMO–HOMO (highest occupied molecular orbital) gap, usually represented by E g , is related to the electronic conduction56. The electron affinity and E g values of the proceeding intermediate are depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…According to molecular orbital theory, a lower lowest unoccupied molecular orbital (LUMO) energy means a larger electron affinity and higher reduction potential, while the LUMO–HOMO (highest occupied molecular orbital) gap, usually represented by E g , is related to the electronic conduction56. The electron affinity and E g values of the proceeding intermediate are depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A similar chelating coordination bonding model has also been demonstrated to account for the enhanced cycling performance when a redox-active quinone-based organic polymer was used in Li-ion batteries. [17] In addition to the overall improved long-term cycling performance of 14PAQ, the rapid capacity loss in the first few cycles also deserves attention. We speculate that the two adjacent carbonyl groups (C=O) could only stably accommodate one inserted magnesium cation species due to the induced steric hindrance resulted from the chelating interaction.…”
Section: Doi: 101002/aenm201600140mentioning
confidence: 99%
“…It is widely known that the formation of the SEI film is a very common phenomenon for the anode materials during the initial discharge process [31,32]. Even though, the initial reversible capacity is much better than most of the thioether or thianthrene bond-containing compounds [20,[33][34][35][36], indicating a superiority of PDB over them. Additionally, the potential plateaus observed in the charge-discharge profiles show good consistent with the redox peaks in the CV curves.…”
Section: Science China Materialsmentioning
confidence: 99%
“…Apart from the carbonyl bonds that provided the reactive centers for the redox reactions, the thioether bonds was found to greatly enhance the conductivity of the electrode and thus leaded to a high stability of the electrode. More recently, polyanthraquinone (PAQ) and lithium salt of poly(2,5-dihydroxy-p-benzoquinonyl sulfide) (Li 2 PDHBQS) were also discovered to have the ability to deliver excellent cycling stability after ultra-long charge-discharge cycles [18,20]. The extraordinary electrochemical results of these polymers indicated that quinone-based polymers with the thioether bond could effectively improve the redox reactivity as well as prevent the unwanted dissolution of the organic compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation